Deje $r,s,t$ ser las raíces. Por simplicidad, escribir $B=-b/a=r+s+t$, $C=c/a=st+tr+rs$, e $D=-d/a=rst$. Deje $p= \frac{r}{s}+\frac{s}{t}+\frac{t}{r}$ e $q=\frac{s}{r}+\frac{t}{s}+\frac{r}{t}$. A continuación,
$$p+q=\frac{r^2(s+t)+s^2(t+r)+t^2(r+s)}{rst}.$$
$$pq=3+\frac{r^4st+s^4tr+t^4rs+s^3t^3+t^3r^3+r^3s^3}{r^2s^2t^2}.$$
Es decir,
$$p+q=\frac{BC-3D}{D}$$
y
$$pq=3+\frac{C^3+B^3D-6BCD+6D^2}{D^2}=\frac{C^3+B^3D-6BCD+9D^2}{D^2}.$$
Por lo tanto, $p$ e $q$ son las raíces de
$$x^2-\frac{BC-3D}{D}x+\frac{C^3+B^3D-6BCD+9D^2}{D^2},$$
que es el mismo que
$$x^2+\frac{3ad-bc}{ad}x+\frac{9a^2d^2-6abcd+ac^3+b^3d}{a^2d^2}.$$
Por ejemplo, $B=6$, $C=11$, e $D=6$ dar $$x^2-8x+\frac{575}{36}=\left(x-\frac{23}{6}\right)\left(x-\frac{25}{6}\right).$$
De hecho, $\{r,s,t\}=\{1,2,3\}$, lo $$\{p,q\}=\left\{\frac12+\frac23+\frac31,\frac21+\frac32+\frac13\right\}=\left\{\frac{25}{6},\frac{23}{6}\right\}.$$